PECULARITIES OF KALAMBUR IN SPANISH AND UZBEK LANGUAGES - Kadirov, Boburjon (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
Debates concerning the language that facilitate the communication among the various peoples and nations of the world have persisted. Many ethnic groups and countries make an effort to indicate the diversity of their original language. It is important to note that there are arguments regarding the potential of the language to infer something about the language’s culture through examining the humor subgenres in this society. Kalamburs are one of the genres that best capture the language’s versatility, the variety of meanings it may convey, and the context of tradition and culture. Furthermore, scientists havedifferent views about classifying kalambur’s, origin and background. As a result, it is feasible to examine a variety of historical instances of the word kalambur. Furthermore, the degree to which the kalambur is actively represented in the language is determined by the existence of multiple historical narratives that associate this word with the names of places across multiple nations.This article deals with the structure of the kalambur in Spanish and Uzbek languages, its emergence as a term, the main reasons for its active use by mankind, the etymology, and its specific features.
Keywords: languagel communicationl kalambur; context; polysemy; humor; comic genre; bilingual culture; homograph; homophone; paronomasia; xenomorph